Pengaruh Video Edukasi terhadap Pengetahuan Remaja Putri tentang Kehamilan Tidak Diinginkan Di Kelas IX SMP Negeri 1 Sliyeg Tahun 2025 - Krisnayanti; Evy Ernawati; Novita Puspita Dewi (STIKES Columbia Asia Medan, 2025)
Unwanted pregnancy (UP) among adolescents is a reproductive health problem that affects physical, psychological, social, and economic aspects. Adolescents often lack knowledge about pregnancy and reproductive health. Therefore, effective educational methods, such as video media, are needed to increase adolescent girls’ understanding of UP. This study used a quantitative pretest-posttest design without a control group. Forty-eight ninth-grade students at SMPN 1 Sliyeg were the respondents. Data was collected using a questionnaire before and after intervention using educational video. Data were analyzed using Wilcoxon test to see the difference in knowledge levels. The pretest results showed that 66.7% of respondents had poor knowledge, and none had good knowledge. After the intervention, all respondents (100%) had good knowledge. The Wilcoxon test showed a p-value of 0.000 (<0.05), indicating a significant difference. Therefore, educational video is effective in increasing knowledge of adolescent girls regarding unwanted pregnancy.